Customer’s Satisfaction In ATM Service: An Empirical Study 0f Banks In Chandigarh" accepted for publication in online research journal - Kaur, Manpreet (IJRCM, 2013)
The trend in banking has evolved from cash economy and transformed to cheque economy which has further been converted to plastic card economy. The study reveals the various dimensions of SERVQUAL (service quality) and its effect on the customer satisfaction. In this regard, primary data was collected from the 120 respondents who are the customers of Andhra Bank and ICICI banks of Vijayawada city through a structured questionnaire. Data was tabulated and analyzed with the help of statistical tools to achieve the objective of the study